Global Uncertainty and Indonesian Stock Performance: Evidence on JCI Volatility using ARCH-GARCH & ARDL - Maruf, Muhammad Sulton; Setyowati, Eni (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This research examines the influence of three dimensions of global uncertainty-Global Economic Policy Uncertainty (GEPU), Global Geopolitical Risk (GPR), and the Global Financial Stress Index (GFSI) on the volatility of Indonesia's stock market, specifically the Jakarta Composite Index (IHSG). Volatility is quantified employing a GARCH(1,1) model utilizing daily IHSG returns spanning from 2019 to 2025, subsequently transformed into monthly data for analytical purposes through the Autoregressive Distributed Lag (ARDL) methodology, incorporating inflation and the Bank Indonesia Rate as domestic control variables. The Bound Test substantiates a long-term relationship between global uncertainty and IHSG volatility. Long-term estimations indicate that both GEPU and GFSI significantly amplify volatility, whereas GPR exerts a notable negative influence, implying that Indonesia functions as a relatively secure haven amid global geopolitical strife. Inflation mitigates volatility, while the BI Rate appears to be statistically insignificant. In the short-term context, only GFSI displays a direct impact. The substantial error correction term (-0.83) signifies a robust tendency toward equilibrium restoration. Overall, global systematic risks predominantly overshadow domestic factors in determining the volatility of Indonesia's financial market.